2017
DOI: 10.1037/fam0000208
|View full text |Cite
|
Sign up to set email alerts
|

Childhood abuse and later marital outcomes: Do partner characteristics moderate the association?

Abstract: Although people with a history of child abuse are known to be at elevated risk for later difficulties in relationships, there is debate over whether these effects are enduring and relatively immutable or whether they are moderated by characteristics and behaviors of the partner. To reconcile these competing perspectives, we conducted a longitudinal study of 414 newlywed couples living in low-income neighborhoods, testing whether the association between abuse history and relationship satisfaction is dependent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 55 publications
2
28
0
1
Order By: Relevance
“…For example, CM has been shown to be a risk factor for teenage motherhood (Madigan et al, 2014), and it is well documented that early motherhood is linked to problems in parenting (Tarabulsy et al, 2005). Likewise, it is possible that CM exposed parents experience relationship instability with their partner and that this may affect their ability to provide a stable home environment for their child (Nguyen, Karney, & Bradbury, 2017). CM must be viewed as only one of the numerous characteristics that have a bearing on the quality of parenting behaviors, but its importance varies as a function of the degree to which it is embedded within the more global developmental ecology of the parent–child dyad.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CM has been shown to be a risk factor for teenage motherhood (Madigan et al, 2014), and it is well documented that early motherhood is linked to problems in parenting (Tarabulsy et al, 2005). Likewise, it is possible that CM exposed parents experience relationship instability with their partner and that this may affect their ability to provide a stable home environment for their child (Nguyen, Karney, & Bradbury, 2017). CM must be viewed as only one of the numerous characteristics that have a bearing on the quality of parenting behaviors, but its importance varies as a function of the degree to which it is embedded within the more global developmental ecology of the parent–child dyad.…”
Section: Discussionmentioning
confidence: 99%
“…In that respect, a study by Colman and Widom (2004) revealed that adult interpersonal trauma survivors were twice as likely as non-survivors to get divorced. Several studies also observed that survivors tend to avoid intimate relationships, reporting that they fear being hurt or revictimized (Rumstein-McKean & Hunsley 2001;Staples et al 2012), and that they are at higher risks of couple distress as well as intimate partner violence (Bigras et al 2015;Godbout et al 2007;Nguyen et al 2017). Significant links were also found between posttraumatic avoidance behaviors and relational commitment difficulties (Staples et al 2012).…”
mentioning
confidence: 98%
“… 1. Other papers have been published using portions of data from this sample to investigate other research questions (e.g., how a history of child abuse predicts marital satisfaction, Nguyen, Karney, & Bradbury, 2016; how marital satisfaction is reciprocally associated with couple communication over time, Lavner, Karney, & Bradbury, 2016), but this is the first to use five waves of data and the first to use group-based trajectory modeling. …”
mentioning
confidence: 99%